Mapping Africa's advanced public health education capacity: the AfriHealth project - CB IJsselmuiden; TC Nchinda; S Duale; NM Tumwesigye; D Serwadda (The World Health Organization, 2007)
OBJECTIVE: Literature on human resources for health in Africa has focused on personal health services. Little is known about graduate public health education. This paper maps "advanced" public health education in Africa. Public health includes all professionals needed to manage and optimize health systems and the public's health. METHODS: Data were collected through questionnaires and personal visits to departments, institutes and schools of community medicine or public health. Simple descriptive statistics were used to analyse the data. FINDINGS: For more than 900 million people, there are fewer than 500 full-time staff, around two-thirds of whom are male. More men (89%) than women (72%) hold senior degrees. Over half (55%) of countries do not have any postgraduate public health programme. This shortage is most severe in lusophone and francophone Africa. The units offering public health programmes are small: 81% have less than 20 staff, and 62% less than 10. On the other hand, over 80% of Africans live in countries where at least one programme is available, and there are six larger schools with over 25 staff. Programmes are often narrowly focused on medical professionals, but "open" programmes are increasing in number. Public health education and research are not linked. CONCLUSION: Africa urgently needs a plan for developing its public health education capacity. Lack of critical mass seems a key gap to be addressed by strengthening subregional centres, each of which should provide programmes to surrounding countries. Research linked to public health education and to educational institutions needs to increase.